PERSEPSI GURU EKONOMI TERHADAP INSTRUKSI GUBERNURLARANGAN PENGGUNAAN HANDPHONE DALAM PEMBELAJARAN DI ERA DIGITAL - Arya Deni Saputra (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2026)
This study aims to determine the perceptions of economics teachers regarding the development of digital technology, perceptions regarding Governor's Instruction Number 8 of 2025 concerning the prohibition on the use of mobile phones in learning, and teachers' strategies in dealing with this policy. This research used a qualitative approach with a case study method at SMA Negeri 13, Jambi City. The research informants consisted of the principal, the vice principal for curriculum, and the economics teacher. Data were collected through interviews, observation, and documentation, then analyzed using NVivo using data reduction, data presentation, and conclusion drawing techniques. Research shows that economics teachers have a positive perception of the development of digital technology because it can improve learning effectiveness, expand access to information, and support students' digital literacy. However, teachers expressed a dilemma regarding the policy banning cell phone use. On the one hand, the policy is considered capable of improving student discipline and focus on learning. On the other hand, the policy limits the use of technology to support economics learning. To overcome these limitations, teachers implemented various strategies, such as utilizing alternative learning media, utilizing school technology facilities, implementing contextual learning, and assigning digital-based assignments outside of school hours. Examining economics teachers' perceptions of the newly implemented mobile phone ban policy in Jambi Province. This specific study examined economics teachers' perceptions of Jambi Governor's Instruction Number 8 of 2025.